PROSTATIC CAPSULAR ARTERY RESISTIVE INDEX AND MALE BLADDER OUTLET OBSTRUCTION - Soebadi, Moh. Ayodhia; Djojodimedjo, Tarmono; Wirjopranoto, Soetojo; P, Widodo J (Indonesian Urological Association, 2013)
Objective: This study aims to explore the relationship between resistive index (RI) with clinical parameters and degree of bladder outlet obstruction (BOO). Materials & Methods: We performed clinical examination which included IPSS, uroflowmetry, transrectal prostate ultrasonography for measurement of prostatic volume and RI of prostatic capsular artery, and pressure flow study. We enrolled patients with lower urinary tract symptoms (LUTS) and prostatic volume of more than 20 ml. Statistical analysis utilised correlation and calculation of sensitivity, specificity, and area under curve of receiver operating characteristics. Results: Twenty-six patients provided consent to enroll in this study. Mean age was 66,5 ± 6,56 years, mean IPSS was 15,9 ± 7,27, and mean prostatic volume 36,0 ± 23,78. Kolmogorov-Smirnov test showed normal distribution of all study variables. There was significant correlation between RI and IPSS, Qmax, and BOO (p < 0,05). Correlation coefficients (r) for prostatic volume and BOO was 0,392 (p = 0,048), for Qmax and BOO was -0.515 (p = 0,007), and RI with BOO was 0,414 (p = 0,035). Using cutoff values for RI ≥ 0,70 and BOO ≥ 4, we found sensitivity of 70,0%, specificity of 50,0%, positive predictive value of 46,7% and negative predictive value of 72,7%. Conclusion: Resistive index of prostatic capsular artery is correlated with BOO and has a role in diagnosis of BOO in men with LUTS related toBenign Prostatic Hyperplasia (BPH).Keywords: Resistive index, transrectal power doppler ultrasonography, lower urinary tract symptoms, bladder outlet obstruction.